2017
DOI: 10.1121/1.4977236
|View full text |Cite
|
Sign up to set email alerts
|

Covert cavitation: Spectral peak suppression in the acoustic emissions from spatially configured nucleations

Abstract: Dual laser-nucleation is used to precisely configure two cavitation bubbles within a focused ultrasound field of f0 = 692 kHz, in proximity to the tip of a needle hydrophone. With both bubbles responding in the f0/2 sub-harmonic regime, confirmed via ultra-high speed shadowgraphic imaging, an emission spectrum with no sub-harmonic content is demonstrated, for an inter-bubble spacing ≈λ0. A spectral model for periodic shock waves from multiple nucleations demonstrates peak suppressions at nf0/2 when applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…4. This is due to the fact that the timings between respective shocks are not well replicated between the two representations, and therefore high frequency content is not adding at the correct phases in the simulated acoustic emissions [4,13]. From the results presented in Fig.…”
Section: B F 0 /3 Regimementioning
confidence: 82%
“…4. This is due to the fact that the timings between respective shocks are not well replicated between the two representations, and therefore high frequency content is not adding at the correct phases in the simulated acoustic emissions [4,13]. From the results presented in Fig.…”
Section: B F 0 /3 Regimementioning
confidence: 82%
“…Acoustic cavitation bubbles generated by intense ultrasound in water radiate secondary ultrasound called acoustic cavitation noise owing to their volumetric oscillation. [1][2][3][4][5] In sonochemistry, which is concerned with understanding the chemical effects associated with acoustic cavitation phenomena, [6][7][8][9][10][11] acoustic cavitation noise has been attracting attention as a method for monitoring acoustic cavitation conditions, and numerous research findings have been reported. [12][13][14][15][16][17] However, reports on the explicit use of acoustic cavitation noise other than monitoring are limited.…”
Section: Introductionmentioning
confidence: 99%
“…PAM techniques use the FUS transducer as the emitter while a receiver array passively records the backscattered signal. PAM techniques are extensively characterized and are an improvement compared to conventional PCD monitoring, which has a poor spatiotemporal resolution as it can only detect cavitation events from a fixed volume and can lead to misinterpretation since signals from acoustic events can interfere with each other (Song et al 2017). Spatial resolution can be improved with the use of linear arrays and passive beamforming methods (Gyongy andCoussios 2010, Haworth et al 2017) but given that no imaging pulse is emitted, the axial resolution is suboptimal.…”
Section: Introductionmentioning
confidence: 99%